International Trade Concept: Analysis of Letters of Credit, Custom Bonds and Export-Import Regulations - Murdiono, Jatmiko; Yuliastuti, Hilda; Kamsariaty, Kamsariaty; Purwoko, Harry; Wahyu Putra, Christophorus Indra (Dinasti Publisher, 2024)
The scientific literature review article entitled Concept of International Trade: Analysis of Letter of Credit, Custom Bonds and Export-Import Regulations is in the domain of operational management science. The purpose of this article is to formulate a hypothesis regarding the relationship between various aspects, which will then be used as the basis for further research. This study uses a qualitative descriptive research methodology. The data used in this study comes from previous studies that are still relevant to this study. Information was collected from leading scientific online platforms, such as Publish or Perish, Google Scholar, DOAJ, and the Sinta journal. The results obtained from this study are presented as follows: 1) Letter of credit influences the Concept of international trade; 2) Custom bonds influence the concept of international trade; and 3) Export import regulations influence the concept of international trade.